2018
DOI: 10.4018/978-1-5225-5026-6.ch014
|View full text |Cite
|
Sign up to set email alerts
|

Public Services Through Multi-Channel Issues and Challenges

Abstract: The objective of this chapter is 1) to understand multi-channel architecture, integration, and management; 2) to develop a framework for citizen relationship and grievance management system for a single view; 3) as a case study, to propose framework applied to find what types of channels are providing to the citizens get access to the public services at National, State, and Local level in India; 4) as a case study, to find out challenges and issues with implementation of multi-channel services delivery. The ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In other words, to understand the performance of e-agriculture, particularly from the users' perspective, it is vital to examine the adequate access to IT tools, user-friendly workoriented content, communities of practice, a culture of knowledge, capacity of learning, a spirit of cooperation, commercial and other incentives, and carefully measured capital investments and returns. Paying close attention to all the parameters of the 8Cs framework, it can be assisted to examine the success of IT practices in any sector [24,21,26,25]. Extensive review of the prior studies revealed that 8Cs framework is widely used to examine the readiness of egovernment, knowledge management practices and e-readiness in higher education.…”
Section: Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, to understand the performance of e-agriculture, particularly from the users' perspective, it is vital to examine the adequate access to IT tools, user-friendly workoriented content, communities of practice, a culture of knowledge, capacity of learning, a spirit of cooperation, commercial and other incentives, and carefully measured capital investments and returns. Paying close attention to all the parameters of the 8Cs framework, it can be assisted to examine the success of IT practices in any sector [24,21,26,25]. Extensive review of the prior studies revealed that 8Cs framework is widely used to examine the readiness of egovernment, knowledge management practices and e-readiness in higher education.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…In this line, Rao [23] considered the 8Cs: connectivity (affordability and widespread of ICT devices), content (useful of content and generate in local language), community (forum to discuss the issues), commerce (infrastructure for ecommerce), capacity (human resources such as technical, managerial, policy and legal to use ICTs), culture (forward-looking progressive influence to use ICTs), corporation (governmental support to use ICTs) and capital (adequate financial resources to use ICTs) as the checklist to measure the capacity of any country to be elaborate in e-readiness to make efficient businesses models or develop new export sectors. Rao's framework is furthered utilized to access the citizens' access to ICT on the performance of e-government [24,25] readiness of knowledge management practices by employees in IT companies such as JD Edwards, EDS, EMC, Novell, Open Text, Oracle, SAS, Sun Philippines and Xerox [26] and e-readiness in higher education context [21].…”
Section: Literaturementioning
confidence: 99%
“…G2C networks are expected to be d e s i g n e d b a s e d o n m u l t i -c h a n n e l communication options to allow the government to support more citizens as much as possible (Rao, 2018). Although the internet and information kiosks are the necessary means of providing government services and information to individuals, other channels such as computers, emails and mobile technologies remain relevant in G2C interactions (Rao, 2018). However, ICT penetration within the local community in developing countries remains a significant obstacle to implementing e-government (Asongu & Le Roux, 2017).…”
Section: Citizens' Access To Ictmentioning
confidence: 99%
“…Similarly, in more industrialised economies and developed nations with wider smartphone use, governments experience providing services and information through mobile technologies. Therefore, the achievement of G2C by the citizens is, largely dependent on access to multi-channel distribution methods (Rao, 2018).…”
Section: Citizens' Access To Ictmentioning
confidence: 99%